Urgensi Mahar sebagai Bentuk Komitmen dalam Ikatan Pernikahan Islam - Rudi Hartono I; Ali Asman; Ridho Wahyudi Siregar; Muhammad Ghufron; Abdullah Rifa’i (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Mahr in Islamic marriage plays a significant role as a symbol of commitment, respect, and protection of women's rights. This study aims to analyze the urgency of mahr in Islamic marriage, from the perspectives of Islamic law, the responsibilities of men, and the protection of women. Using a literature review approach, this research explores relevant literature on mahr in the context of Islamic law, hadith, and the views of scholars regarding the meaning and purpose of mahr. The results show that mahr is not only a financial obligation but also a deep form of respect and commitment between partners. However, in contemporary social practices, there are deviations in the understanding of mahr, which is often viewed as a status symbol or materialistic transaction. This study concludes that to maintain the values of Islam in marriage, the understanding of mahr must return to the essence taught by Islam, which is as a form of responsibility, simplicity, and respect for women.